Investigation of the Tribological Impact of the Tool Radius on a Strip Drawing Test Rig With Redirection - He, Franz; Merklein, Marion (9th International Conference on Hot Sheet Metal Forming of High-Performance Steel, CHS2 2024 - Proceedings, 2024)
With the rise in electric vehicles, the focus on the reduction in the overall weight of the personalized motorized vehicle provides a central focus point in the automotive industry. Hot stamping has been established as a suitable process for the generation of critical structural components in the body in white which provide improved strength and stiffness at reduced component weight. Due to the high process temperatures suitable lubricants have not yet been found. Direct results are both high friction and occurrences of wear on both tool and workpiece. To characterize the tribological conditions in the hot stamping process flat strip drawing tests have been commonly used. These however only accurately represent the flange area of a workpiece, while the critical sheet thinning can be observed at radii where the additional bending motion changes the contact conditions. To properly reproduce the tribological conditions in the tool radius area an existing strip drawing test rig at the Institute of Manufacturing Technology has been modified to allow for a strip drawing test with redirection. Using the test rig in combination with the results of a simulation of the process allows for an inverse determination of the friction coefficients present. The results of this study help to improve the process understanding of the contact and tribological conditions in the tool radius area in the hot stamping process. Furthermore tailored measures can be developed based on the findings of this study to improve the part quality and overall tool lifetime.
CRIS-Team Scopus Importer:2024-07-19